Toluene and its Derivatives as Atom-Efficient Benzylating Agents for Secondary Amines - Schönbauer, David; Lukas, Florian; Schnürch, Michael (Synlett, 2019)
Toluene as a replacement for common N-benzylating agents, such as benzyl bromide, can be an atom-efficient alternative reagent. Under nickel catalysis and mildly oxidative conditions, it is possible to activate toluene efficiently and use it directly for the benzylation of different 2-aminopyridines. The transformation is not restricted to simple toluene, but also substituted derivatives give the desired product in good yields. Effective cleavage of the pyridine moiety is presented.
Keywords: C–H functionalization; benzylation; nickel catalysis; toluene activation; amines